Central sympathetic nervous system reinforcement in obstructive sleep apnoea - Wszedybyl-Winklewska, Magdalena; Wolf, Jacek; Szarmach, Arkadiusz; Winklewski, Pawel J; Szurowska, Edyta; Narkiewicz, Krzysztof (Sleep medicine reviews, 2018)
The available studies on cerebrovascular reactivity and cerebral oxygenation in obstructive sleep apnoea (OSA) patients brought conflicting results, yet the overall evidence suggests that resting state cerebral perfusion is diminished in these patients. Interestingly, in a group of healthy professional breath-hold divers who are exercising very long apnoeas - episodes corresponding to the ones observed in patients with OSA - demonstrated that cerebral oxygenation may remain stable at the expense of extreme sympathetic nervous system (SNS) activation. In the present review we address several mechanisms that could potentially explain these discrepancies. We focus in depth on mechanisms of central SNS reinforcement in OSA including dysfunctional baroreflex response, and inflammatory processes within the brain centres controlling the cardiovascular system. Additionally, novel insights into physiology of cerebral blood flow regulation are proposed, including the role of short-term blood pressure changes, heart rate fluctuations and baroreflex alterations. Finally, a potential role of increased blood flow pulsatility in cerebrospinal fluid circulation changes and its influence on SNS drive is highlighted. The presented review provides insights into how sympathetic nervous system reinforcement in OSA promotes maladaptive mechanisms that could alter cerebral perfusion regulation, and result in functional and structural cerebral changes.
Keywords: Functional neuroanatomy; Baroreflex; baroreflex; kardiovaskulární systém; krevní tlak; Autonomic regulation; mozkový krevní oběh; Cerebral perfusion; Cardiovascular System; mozek; Heart Rate; srdeční frekvence; Sleep Apnea, Obstructive; Brain; Central nervous system; Blood Pressure; Humans; Cerebrovascular Circulation; sympatický nervový systém; Sympathetic Nervous System; obstrukční spánková apnoe; Obstructive sleep apnoea; lidé